Efficiency and Safety of Proprotein Convertase Subtilisin/Kexin 9 Monoclonal Antibody on Hypercholesterolemia: A Meta‐Analysis of 20 Randomized Controlled Trials. Issue 6 (15th June 2015) - Li, Chuanwei; Lin, Ling; Zhang, Wen; Zhou, Liang; Wang, Hongyong; Luo, Xiaoli; Luo, Hao; Cai, Yue; Zeng, Chunyu
Abstract : Background: Proprotein convertase subtilisin/kexin9 (PCSK9) monoclonal antibody significantly reduces low‐density lipoprotein cholesterol level in patients with hypercholesterolemia. The goal of this study was to review recently reported randomized controlled trials to investigate the therapeutic effects and safety of PCSK9 inhibitors. Methods and Results: The clinical randomized controlled trials published from inception to March 19, 2015 were identified from The Cochrane Library databases, PUBMED, and EBASE. Randomized controlled trials of at least 8 weeks duration using PCSK9 inhibitors in treating patients with hypercholesterolemia were included. Mean difference (MD) with a 95% CI was used to calculate the continuous data, the standardized mean difference with a 95% CI was used when the unit was not unified, and risk ratio with a 95% CI was used for dichotomous data. After screening, 20 trials fulfilled the inclusion criteria. PCSK9 inhibitors significantly decreased the levels of low‐density lipoprotein cholesterol (MD=−65.29 mg/dL, 95% CI: −72.08 to −58.49), total cholesterol (MD=−60.04 mg/dL, 95% CI: −69.95 to −50.13), triglycerides (MD=−12.21 mg/dL, 95% CI: −16.21 to −8.22) and apolipoprotein‐B (MD=−41.01 mg/dL, 95% CI: −46.07 to −35.94), lipoprotein(a) (standardized mean difference=−0.94, 95% CI: −1.12 to −0.77) and increased the levels of high‐density lipoprotein cholesterol (MD=3.40 mg/dL, 95% CI: 3.12 to 3.68) and apolipoprotein‐A1 (MD=6.75 mg/dL, 95% CI: 4.64 to 8.86). There was no significant difference in the incidence of treatment‐emergent adverse events (risk ratio=1.01, 95% CI: 0.98 to 1.04), serious treatment‐emergent adverse events (risk ratio=1.01, 95% CI: 0.88 to 1.17), and the discontinuation of treatment between the 2 groups (risk ratio=1.07, 95% CI: 0.86 to 1.34). Conclusions: The meta‐analysis indicated that PCSK9 inhibitors had a strong effect in lowering low‐density lipoprotein cholesterol and other lipid levels with satisfactory safety and tolerability in patients with hypercholesterolemia.